2001
DOI: 10.1046/j.1439-0485.2001.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Community Structure of the Intertidal Macroinfauna and Sandy Beach Characteristics Along the Chilean Coast

Abstract: Abstract. Eight sandy beaches were seasonally sampled along the coast of Chile, from ca. 21 to 42° S (about 3000 km) to study the relationship between community structure of the intertidal macroinfauna and beach characteristics. Sediment samples (0.1 m2, 30 cm deep) were collected (July – September 1998 and December 1998 – January 1999) with plastic cylinders at 15 equally spaced levels along three replicated transects extending from above the drift line to the swash zone. The sediment was sieved through a 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 16 publications
2
36
1
2
Order By: Relevance
“…Dugan & Hubbard (1994) found that in sandy beaches of southern California, E. analoga had similar population abundances at reflective and intermediate beaches. Similarly, Jaramillo & Lastra (2001) and Jaramillo et al (2001) showed that on the Chilean coast, E. analoga displays the highest population abundances at intermediate beaches such as Calfuco. In some intermediate beaches, estimations of mean population abundances of E. analoga have been found to be 4-6 times higher than in dissipative sites .…”
Section: Discussionmentioning
confidence: 82%
“…Dugan & Hubbard (1994) found that in sandy beaches of southern California, E. analoga had similar population abundances at reflective and intermediate beaches. Similarly, Jaramillo & Lastra (2001) and Jaramillo et al (2001) showed that on the Chilean coast, E. analoga displays the highest population abundances at intermediate beaches such as Calfuco. In some intermediate beaches, estimations of mean population abundances of E. analoga have been found to be 4-6 times higher than in dissipative sites .…”
Section: Discussionmentioning
confidence: 82%
“…The presence of surf diatom accumulations has led to the definition of dissipative beaches as semi-closed ecosystems (sensu McLachlan 1980), in contrast to reflective beaches, defined as interfaces with low productivity, subsidized by organic inputs from the sea (Brown & McLachlan 1990). Whereas increased wave energy in temperate areas seems to cause increased productivity and biomass, stranded seagrass or algae (Colombini & Chelazzi 2003), or the presence of upwelling (Jaramillo et al 2001) can also add to sand beach energetics and biomass.…”
Section: Latitudinal Patternsmentioning
confidence: 99%
“…There are many studies on the patterns of macrofaunal zonation in exposed sandy beaches of the coastal upwelling system (e.g. Jaramillo et al , 2001, showing that changes in beach morphodynamic result in significant community responses of the intertidal macroinfauna. Communities of sandy beaches of south and central Peru show clear fluctuations of dominant species such as the surf clams Mesodesma donacium and Donax marincovichi, and the sand crab Emerita analoga.…”
Section: Introductionmentioning
confidence: 99%
“…Contreras et al 1999), and is a characteristic specie of the swash zone (Jaramillo et al , 2001Contreras et al 1999). It can appear in high abundance forming aggregations at certain water temperatures, food availability and beach morphodynamics (Perry 1980;Dugan 1994;Contreras et al 1999).…”
Section: Introductionmentioning
confidence: 99%